Analisis Pengaruh Konten Tiktok @yoggi.130 terhadap Minat Berkunjung Pengikut Ke Destinasi Wisata Kabupaten Garut - Irsan Maulana; Hadiati Hadiati; Chotijah Fanaqi (MUKASI: Jurnal Ilmu Komunikasi, 2025)
TikTok has grown into a dominant digital platform that plays a significant role in shaping social interactions, sharing virtual experiences, and distributing information quickly and widely. This study aims to evaluate the extent of the influence of the TikTok account @yoggi.130 on increasing tourist interest and visits to tourist destinations in Garut Regency. This study refers to the AIDA (Attention, Interest, Desire, Action) theory proposed by Kotler and Keller, which highlights the importance of persuasive communication strategies in influencing consumer decisions. Using a quantitative approach, data was collected through a survey of one hundred respondents who are active followers of the account. Data processing out using a simple linear regression model with the help of SPSS software version 22. The findings of this study revealed a significant positive correlation between the content published by the TikTok account @yoggi.130 and the level of followers' interest in conducting tourist visits, while the rest was influenced by other variables. These results confirm that the video content presented by @yoggi.130, which is informative, attractive, and consistently produced, is able to build a unique appeal that impacts followers' decisions to visit tourist destinations in Garut Regency.